2021
DOI: 10.3389/fpsyg.2021.669606
|View full text |Cite
|
Sign up to set email alerts
|

The Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale: A New Instrument for Assessing the Anxiety Response of General Population to the Viral Epidemic During the COVID-19 Pandemic

Abstract: The general population has reported experiencing anxiety due to the COVID-19 pandemic. This study explored the validity and utility of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale for measuring the anxiety response of the general population to the viral epidemic. About 1,009 respondents participated in an online survey. Of these, 501 (49.7%) participants were rated as having at least a mild degree of anxiety response to the viral epidemic (SAVE-6 score ≥ 15), while 90 (8.9%) and 69 (6.8%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
99
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 22 publications
13
99
1
Order By: Relevance
“…", due to the high proportion of the responses of "never" (45.8%) and "rarely" (36.8%). This result was similar to that of our previous study of SAVE-6 applied to the general Korean population (8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…", due to the high proportion of the responses of "never" (45.8%) and "rarely" (36.8%). This result was similar to that of our previous study of SAVE-6 applied to the general Korean population (8).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, a single-structure model of SAVE-6 was confirmed to be valid and in line with previous studies (8,9). However, we observed a relatively low factor loading value of 0.446 for item 1, "Are you afraid that the virus outbreak will continue indefinitely?"…”
Section: Discussionsupporting
confidence: 91%
“…Previously, among healthcare workers, for whom the original SAVE-9 scale was developed, 3 the optimal cut-off score for factor I (anxiety about the viral epidemic) was ≥ 15 points. In other studies, on the Korean version of the SAVE-6 scale applied to the general population, SAVE-6 scores of 15 (sensitivity = 70.7%, specificity = 60.0%) and 17 points (sensitivity = 72.5%, specificity = 71.3%) were consistent with at least mild (≥ 5) and moderate (≥ 10) degrees of anxiety according to the GAD-7 scale, 2 respectively. A more severe pandemic situation in Lebanon may have influenced the lower SAVE-6 scale cut-off score.…”
mentioning
confidence: 65%
“…Recently, the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale was developed in South Korea as a tool to assess such anxiety in the general population. 2 The tool is based on factor I (anxiety about the viral epidemic) from the original SAVE-9 scale that was developed for healthcare workers. 3 This study aimed to explore the psychometric properties of the Arabic version of the SAVE-6 scale as a tool for assessing anxiety in response to the viral epidemic among university students in Lebanon.…”
mentioning
confidence: 99%
See 1 more Smart Citation